Optimización de la distribución de peajes en la red vial principal de Ecuador, para recaudar el monto necesario para el mantenimiento del sistema (2017)
"The transport network maintenance is one of the objectives of the mobility master plans. Financing alternatives to achieve this challenge are divided in taxes and users charges. This document proposes an optimization model for toll distribution in to the principal road network of Ecuador with a sustainability framework. In order that, the total income of the system guarantee the resources to maintenance all roads of the system. The model includes in its objective functions an economic and social component. The results could be used in decision making process about location of tolls and network management." -- Tomado del Formato de Documento de Grado.